The human dimension in the history of the goddess Shaooshka Analytical theory of the country of Subarto - ancient kurdistan - مامۆستاى یاریدەدەر ئارەزوو ڕەسوڵ ئەحمەد, (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
This article is a triggering point to some independent researches about the deities worshipped in Kurdistan prior to the Christianity, one of which was the goddess “Shawshka”. Statues made of mud have been found in the ancient settlements such as Sarpeli Zahaw, Hawler, Noozi, Amed,…etc, and all of them were in the shape of a female. Archeologists and historians believe that those statues must have represented the mother goddess. Human beings (both male and female genders) have from the childhood the image of mother in their mind, since mothers are the ones who play the most important role in bringing up children, hence the cuddle of mother stays as the warmest and safest place for children. In the Paleolithic and Neolithic eras, the class and level of mothers were different from those of the contemporary mothers. This article studies scientifically the role of “Shawshka” as the goddess of mother, love and war in the era of matriarchy. This research is an attempt to rewrite the feminine history in Kurdistan because many aspects of our feminine history, either hasn’t been mentioned or has been ignored. Key words: gynocentrism, matriarchy, Shawshka goddess, the Hurians, Kurdistan, mother goddess.